Supported FeCo alloy bimetallic catalyst as well as preparation method and application thereof

By using BaZr0.1Ce0.7Y0.1Yb0.1O3-δ as support, the FeCo alloy catalyst was prepared, which solved the problem of reforming in the ammonia decomposition catalyst in PCFC anode, achieved efficient ammonia decomposition and stability, and reduced energy consumption and carrier cost. , suitable for large-scale applications.

CN119186574AInactive Publication Date: 2024-12-27NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411290303.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, it is difficult to achieve internal reforming of ammonia decomposition catalysts in PCFC anodes, resulting in low energy utilization efficiency and complex devices, and the commonly used metal oxide carriers are costly and difficult to apply on a large scale.

Method used

BaZr0.1Ce0.7Y0.1Yb0.1O3-δ as support is used to prepare FeCo alloy bimetallic catalyst. Through ultrasonic oscillation and drying and calcining, FeCo alloy nanoparticles are formed to realize internal and external reforming of the catalyst, reduce energy consumption, and pass The synergistic action of Fe and Co improves ammonia decomposition activity and stability.

Benefits of technology

Reforming in the ammonia decomposition catalyst in the PCFC anode is achieved, energy utilization is saved, the long-term stability and catalytic activity of the catalyst is improved, the production of nitrogen oxides is reduced, and the support cost is relatively low, which is suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186574A_ABST
    Figure CN119186574A_ABST
Patent Text Reader

Abstract

The invention provides a supported FeCo alloy bimetallic catalyst as well as a preparation method and application thereof, and the preparation method specifically comprises the following steps: respectively adding Fe (NO3) 3.9 H2O, Co (NO3) 2.6 H2O and BaZr0. 1Ce0. 7Y0. 1Yb0. 1O3-delta into absolute ethyl alcohol, uniformly stirring, pouring into an active metal salt solution, oscillating to uniformly distribute the active metal and the catalyst, and sequentially drying, grinding and calcining the powder to obtain the supported FeCo alloy bimetallic catalyst. According to the invention, BaZr0. 1Ce0. 7Y0. 1Yb0. 1O3-delta is taken as a carrier, Ba is alkaline earth metal, ammonia decomposition catalytic performance can be improved through electron donating effect, the catalyst has the effect of a structure promoter, local arrangement of Fe and Co atom surfaces is changed, the catalyst is an electrolyte material of a proton ceramic fuel cell (PCFC), active metal can be internally reformed into a positive electrode of the PCFC, ammonia is taken as a direct fuel, and the catalyst can be used as a fuel cell. The system integration level and the fuel utilization rate are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a supported FeCo alloy bimetallic catalyst and a preparation method and application thereof. Background Art

[0002] Hydrogen is an ideal and most widely used energy fuel because it has a high combustion value, produces only heat and water, and is clean and pollution-free. However, hydrogen is difficult to liquefy at room temperature, has a low volume energy density, and storage and transportation hinder its large-scale application. Compared with methanol (12.5%), ammonia has a higher hydrogen content of 17wt%, and compared with 4.5 MJ / L of pressurized hydrogen, liquid ammonia has a higher volume density of 12.9 MJ / L, which has higher energy efficiency, is carbon-free, environmentally friendly, has high energy density, and is easy to liquefy (8.5 atmospheres at room temperature). Ammonia is widely used as a fertilizer in crops, so the infrastructure is complete, the storage and transportation costs are lower, the combustion range is smaller, it is safer, and the gas has a pungent smell, and leaks above 1ppm can be detected. Therefore, ammonia is the most promising alternative energy source for hydrogen.

[0003] PCFC (Proton Ceramic Fuel Cell) is an electrochemical device that converts chemical energy directly into electrical energy. It is not limited by the Carnot cycle, has a high energy conversion rate, and produces H2O. It has the advantages of low pollution emissions, high conversion efficiency, and wide fuel applicability. The decomposition products of ammonia are H2 and N2, which can be used as a promising fuel for SOFC. However, when NH3 is directly used as a fuel for PCFC, ammonia cannot be completely decomposed at low temperatures, and the anode nickel is nitrided in NH3, reducing the performance, long-term stability, and thermal cycle stability of PCFC. The decomposition temperature of NH3 is high and ammonia is almost not decomposed at low temperatures. In order to reduce energy waste, an ammonia decomposition catalyst is needed to decompose NH3 to reduce the ammonia decomposition temperature.

[0004] Ru is recognized as the most active single metal catalyst for ammonia decomposition, but Ru is a scarce precious metal and is not suitable for commercial production. Therefore, there is an urgent need to seek cheap transition metals with good catalytic performance, such as Fe and Co. The "volcano-type" curve shows that among transition metals, Co-based catalysts have higher catalytic activity, and the stability of Co can be significantly improved by alloying with Fe.

[0005] On this basis, ammonia decomposition often requires a catalyst carrier, and currently most commonly used ammonia decomposition catalyst carriers are metal oxides, SiO2, CNT and metal oxide composites, etc., which can only be used for external reforming to decompose ammonia in PCFC. In practical applications, an external heat source is required to supply heat energy to decompose ammonia, which reduces energy utilization and makes the device more complicated. Therefore, in the prior art, how to directly reform the active catalytic metal into the PCFC anode is still a problem to be solved. Summary of the invention

[0006] In order to solve the above-mentioned technical problems, the present invention uses BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ As a carrier, it solves the problem of directly internally reforming the active catalytic metal into the PCFC anode and the problem of high carrier cost and difficulty in large-scale application.

[0007] The present invention provides a method for preparing a supported FeCo alloy bimetallic catalyst, and the preparation method specifically comprises the following steps: Combine Fe(NO3)3·9H2O, Co(NO3)2·6H2O and BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The catalyst was added to anhydrous ethanol respectively, stirred evenly, and then the formed carrier suspension was poured into the active metal salt solution, ultrasonically vibrated for 30 min to evenly distribute the active metal and the catalyst, and stirred in a fume hood until the anhydrous ethanol was completely evaporated. The obtained powders were dried, ground, and calcined in sequence to obtain Fe(NO3)3·9H2O, Co(NO3)2·6H2O and BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The mass ratio is 1:(1-1.1):(18-19).

[0008] BZ 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3−δ (BCZYYb) is a complex solid solution material belonging to a composite oxide with a perovskite structure. This material has broad application prospects in solid oxide fuel cells (SOFCs), gas sensors and catalysts due to its excellent electrochemical properties.

[0009] Compared with the prior art, the present invention uses BaZr as the electrolyte material of PCFC. 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δAs a carrier, it is combined with FeCo alloy nanoparticles. The FeCo alloy nanoparticles can perform external reforming and internal reforming on the carrier, greatly saving energy utilization. Among them, Fe can reduce the generation of nitrogen oxides and has good long-term stability. Co has high ammonia catalytic activity. By doping Fe into the Co active metal, both high catalytic activity and long-term stability can be achieved. At the same time, BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The supported FeCo alloy has a synergistic effect. The Fe-based catalyst promotes ammonia decomposition and reduces the generation of nitrogen oxides. Co acts as an electron donor. The formation of FeCo on the surface enables the transfer of electrons to Fe. The change in the electronic properties of Fe is conducive to the desorption of adsorbed N atoms from the surface, thereby reducing the activation barrier of the ammonia decomposition reaction and improving the catalytic activity. Furthermore, in the present invention, BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ is used as a carrier. Among them, Ba is an alkaline earth metal, which can improve the catalytic performance of ammonia decomposition through the electron-donating effect, has the role of a structural promoter, changes the local arrangement of Fe and Co atoms on the surface, and has good industrial application prospects.

[0010] It is worth mentioning that in the present invention, only BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ is used as one of the proton ceramic conducting electrolytes, while other types of Ba-based electrolyte materials by adjusting the proportion of the B-site elements in ABO3 in the perovskite structure and ensuring that the sum of all B-site elements is equal to 1 as alternative choices also have the same or similar effects. For example, BaZr 1-x-y-z Ce x Y y Yb z O 3-δ (0 < x, y, z < 1) and BZCY (BaZr 0.1 Ce 0.2 Y 0.1 O 3-δ ), BCY (BaCe 0.8 Y 0.2 O 3-δ ), because these materials all have similar proton conduction characteristics, and the difference is only the relative change in catalytic activity.

[0011] Compared with the prior art, the present invention adopts the above ratio because different mass ratios between iron salts and carrier materials may affect the performance of the final catalyst. A higher iron content may cause aggregation of active components, thereby reducing the surface area and catalytic activity; conversely, a lower iron content may result in insufficient catalytic efficiency.

[0012] In some embodiments, the active metal salt solution is a nitrate solution, and the concentration is 0.04-0.05 mol / L.

[0013] Compared with the prior art, the present invention adopts nitrate solution because nitrate has high stability, that is, it is conducive to the stability of metal precursors and no other phases are generated; nitrate has good solubility and can be more evenly dispersed on the carrier in the subsequent catalyst preparation process to form a catalyst with uniformly distributed active sites; in the thermal reduction process, NO3 - It is easy to remove and reduce metal ions to metal nanoparticles.

[0014] In some embodiments, the drying parameters are as follows: temperature is 85° C., and time is 24 h.

[0015] Compared with the prior art, the present invention adopts the above-mentioned drying temperature and time to ensure the complete removal of anhydrous ethanol in the catalyst, and to ensure the stability of the catalyst and the smooth progress of subsequent processing. Such drying conditions are conducive to the preparation of high-quality catalysts and prepare for the next step of grinding and calcination.

[0016] In some embodiments, the calcination parameters are as follows: temperature is 600° C., and time is 2 h.

[0017] The second object of the present invention is to provide a supported FeCo alloy bimetallic catalyst prepared by the above preparation method.

[0018] The third object of the present invention is to provide an application of a supported FeCo alloy bimetallic catalyst, wherein the supported FeCo alloy bimetallic catalyst is used in the production of hydrogen by decomposing ammonia.

[0019] In some embodiments, before the ammonia decomposition process, in-situ reduction is first performed. The specific steps of the in-situ reduction are: heating to 600° C. at 3° C. / min under N2 atmosphere, introducing 30 mL / min of H2 for 3 h to completely reduce to a metallic state.

[0020] In some embodiments, in the ammonia decomposition hydrogen production reaction, the flow rate of NH3 is 10 mL / min, and the space velocity of the fuel gas is 6000 L kg -1 h -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a schematic diagram of the preparation process of the present invention; Figure 2 FeCo-BaZr after H2 reduction 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ XRD characterization spectrum of the catalyst; Figure 3 FeCo / BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ NH3 conversion rate of catalyst and quartz wool under different temperature conditions; Figure 4 FeCo / BaZr at 600℃ 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Long term stability of the catalyst. DETAILED DESCRIPTION

[0022] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.

[0023] It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0024] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.

[0025] The technical effects of the present invention are described below in conjunction with specific embodiments.

[0026] Example 1

[0027] like Figure 1 As shown, this embodiment provides a supported FeCo alloy bimetallic catalyst, which is prepared by the following preparation method: 0.0487g Fe(NO3)3·9H2O, 0.0513g Co(NO3)2·6H2O and 0.9g BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Add it to anhydrous ethanol and stir evenly. Then pour the formed carrier suspension into the active metal salt solution, which is a nitrate solution with a concentration of 0.0435 mol / L. Ultrasonic oscillation is performed for 30 min to evenly distribute the active metal and the catalyst. Stir in a fume hood until the anhydrous ethanol is completely evaporated. Dry the obtained powder in an oven at 85°C for 24 h, grind it and calcine it at 600°C for 2 h.

[0028] Example 2

[0029] This embodiment provides a supported FeCo alloy bimetallic catalyst prepared by the following preparation method: 0.0487g Fe(NO3)3·9H2O, 0.0487g Co(NO3)2·6H2O and 0.9g BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Add it to anhydrous ethanol and stir evenly. Then pour the formed carrier suspension into the active metal salt solution, which is a nitrate solution with a concentration of 0.04 mol / L. Ultrasonic oscillation is performed for 30 min to evenly distribute the active metal and the catalyst. Stir in a fume hood until the anhydrous ethanol is completely evaporated. Dry the obtained powder in an oven at 85°C for 24 h, grind it and calcine it at 600°C for 2 h.

[0030] Example 3

[0031] This embodiment provides a supported FeCo alloy bimetallic catalyst prepared by the following preparation method: 0.0487g Fe(NO3)3·9H2O, 0.0535g Co(NO3)2·6H2O and 0.925g BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δAdd it to anhydrous ethanol and stir it evenly. Then pour the formed carrier suspension into the active metal salt solution, which is a nitrate solution with a concentration of 0.05 mol / L. Ultrasonic oscillation is performed for 30 min to evenly distribute the active metal and the catalyst. Stir in a fume hood until the anhydrous ethanol is completely evaporated. Dry the obtained powder in an oven at 85°C for 24 h, grind it and calcine it at 600°C for 2 h.

[0032] Catalyst performance test methods The catalytic activity of the catalyst was tested in a continuous fixed bed quartz reactor. 10 mg of the supported FeCo alloy bimetallic catalyst prepared in Example 1 was mixed with 90 mg of quartz fiber and loaded into the quartz reactor. Part of the quartz fiber was filled on both sides of the quartz tube to fully heat the NH3 before the catalyst was introduced and to capture the catalyst lost due to the airflow. Before the ammonia decomposition process, in-situ reduction was first performed. The temperature was raised to 600°C at 3° / min under N2 atmosphere, and 30 mL / min of H2 was introduced for reduction for 3h until it was completely reduced to a metallic state, and then the temperature was raised to the test temperature for catalyst testing. Pure NH3 was introduced at 10 mL / min, and the fuel gas space velocity (GHSV) was 6000 L kg -1 h -1 The ammonia decomposition conversion rate was tested using an ammonia decomposition rate analyzer. Catalytic tests were performed in the range of 450°C to 650°C. The temperature was stabilized for 30 minutes at each temperature until a steady state was reached, and the required data was recorded at the test temperature.

[0033] Figure 2 FeCo-BaZr after H2 reduction 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ XRD characterization spectrum of the catalyst. It can be found from the figure that all characteristic peaks are FeCo alloy phase and carrier BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ , where the Fe-Co alloy phase was observed at 2θ=44.9°, and the characteristic peak of CoFe2O4 was observed at 2θ=35°, indicating that when Fe and Co are in a certain atomic ratio, Co3O4 and Fe2O3 form a composite metal oxide CoFe2O4.

[0034] Figure 3 FeCo / BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δNH3 conversion rate of catalyst and quartz wool under different temperature conditions, 10 sccm NH3 was introduced, and the space velocity (GHSV) was maintained at 6000 L kg -1 h -1 , the catalyst performance test was carried out at a gradient of 50℃, and the test range was 450-650℃. It can be seen that as the test temperature increases, FeCo / BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The ammonia conversion rate of the catalyst continues to increase; the ammonia conversion rate reaches 100% in the range of 550-650℃, and complete decomposition of ammonia is achieved at a relatively low temperature. The ammonia conversion rates at 500℃ and 450℃ are 64.9% and 26.7% respectively. Figure 4 FeCo / BaZr at 600℃ 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The long-term stability of the catalyst. In the 100h ammonia decomposition test, the ammonia decomposition rate was relatively stable at 100% without attenuation, indicating that FeCo / BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The catalyst is highly efficient and stable.

[0035] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A method for preparing a supported FeCo alloy bimetallic catalyst, characterized in that: The preparation method specifically comprises the following steps: Combine Fe(NO3)3·9H2O, Co(NO3)2·6H2O and BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The Fe(NO3)3·9H2O, Co(NO3)2·6H2O and BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The mass ratio is 1:(1-1.1):(18-19).

2. The method for preparing a supported FeCo alloy bimetallic catalyst according to claim 1, characterized in that: The active metal salt solution is a nitrate solution, and the concentration is 0.04-0.05 mol / L.

3. The method for preparing a supported FeCo alloy bimetallic catalyst according to claim 1, characterized in that: The drying parameters are as follows: temperature is 85° C., and time is 24 h.

4. The method for preparing a supported FeCo alloy bimetallic catalyst according to claim 1, characterized in that: The calcination parameters are as follows: temperature is 600° C., and time is 2 h.

5. A supported FeCo alloy bimetallic catalyst, characterized in that: Prepared by any preparation method of claims 1-5.

6. Use of a supported FeCo alloy bimetallic catalyst as claimed in claim 6, characterized in that: The supported FeCo alloy bimetallic catalyst is used in the production of hydrogen by decomposing ammonia.

7. The use according to claim 7, characterized in that Before the ammonia decomposition process, in-situ reduction is first performed. The specific steps of in-situ reduction are: heating to 600°C at 3°C / min under N2 atmosphere, and introducing 30 mL / min of H2 for 3h to completely reduce to the metallic state.

8. The use according to claim 7, characterized in that In the ammonia decomposition hydrogen production reaction, the flow rate of NH3 is 10 mL / min, and the space velocity of the fuel gas is 6000 L kg -1 h -1 .

Citation Information

Patent Citations

  • Catalyst for hydrogen production through ammonia decomposition and preparation and application methods thereof

    CN117101638A

Cited By

  • Ammonia decomposition catalyst, method for producing same, and method for producing hydrogen

    WO2026191572A1